UX for the web : build websites for user experience and usability - Ritter, Marli; Winterbottom, Cara (Packt Publishing, 2017)
Learn how UX and design thinking can make your site stand out from the rest of the internet. About This Book Learn everything you need to know about UX for your Web Design. Design B2B, B2C websites that stand out from the competitors with this guide Enhance your business by improving customer accessibility and retention. Who This Book Is For If you're a designer, developer, or just someone who has the desire to create websites that are not only beautiful to look at but also easy to use and fully accessible to everyone, including people with special needs, UX for the Web will provide you with the basic building blocks to achieve just that. What You Will Learn Discover the fundamentals of UX and the User-Centered Design (UCD) Process. Learn how UX can enhance your brand and increase user retention Learn how to create the golden thread between your product and the user Use reliable UX methodologies to research and analyze data to create an effective UX strategy Bring your UX strategy to life with wireframes and prototypes Set measurable metrics and conduct user tests to improve digital products Incorporate the Web Content Accessibility Guidelines (WCAG) to create accessible digital products In Detail If you want to create web apps that are not only beautiful to look at, but also easy to use and fully accessible to everyone, including people with special needs, this book will provide you with the basic building blocks to achieve just that. The book starts with the basics of UX, the relationship between Human-Centered Design (HCD), Human-Computer Interaction (HCI), and the User-Centered Design (UCD) Process; it gradually takes you through the best practices to create a web app that stands out from your competitors. You'll also learn how to create an emotional connection with the user to increase user interaction and client retention by different means of communication channels. We'll guide you through the steps in developing an effective UX strategy through user research and persona creation and how to bring that UX strategy to life with beautiful, yet functional designs that cater for complex features with micro interactions. Practical UX methodologies such as creating a solid Information Architecture (IA), wireframes, and prototypes will be discussed in detail. We'll also show you how to test your designs with representative users, and ensure that they are usable on different devices, browsers and assistive technologies. Lastly, we'll focus on ma ...